FeSiAl / MOFs-derived composite wave-absorbing material with dielectric frequency dispersion characteristic and preparation method of FeSiAl / MOFs-derived composite wave-absorbing material
By modifying the dielectric dispersive conductive material on the surface of FeSiAl soft magnetic alloy and composited with the modified MOFs material to form a porous heterostructure nanocomposite absorbing material, the absorption performance of existing absorbing materials in the low-frequency and wide-band bands is solved. The problem of taking into account both the problem has been achieved, and the wideband absorption performance is efficient.
Patent Information
- Application Number
- CN202411313870.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-02-11
AI Technical Summary
When existing wave absorbing materials expand to the low-frequency band, their wave absorbing performance in the higher frequency band will be severely attenuated, making it difficult to achieve both low-frequency and wide-frequency wave absorbing performance.
By chemically modifying the conductive material with dielectric dispersion characteristics to the FeSiAl soft magnetic alloy surface and composited with the polydopamine-modified metal organic frame MOFs-derived material, a porous heterostructure nanocomposite absorbing material is formed.
It improves the impedance matching characteristics of the material, improves its wide-frequency absorption performance, and achieves efficient low-frequency and wide-frequency absorption performance.
Smart Images

Figure BDA0005051551140000111 
Figure HDA0005051551160000011 
Figure HDA0005051551160000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of absorbing materials, and in particular to a porous heterogeneous structure nano-composite absorbing material derived from FeSiAl alloy and MOFs and a preparation method thereof. Background Art
[0002] Stealth capability is an important technical feature of the next generation of weapons and equipment. As one of the important components of stealth technology, stealth material technology can significantly improve the effectiveness of combat platforms, enhance electronic combat capabilities, and improve the survival and penetration capabilities of targets. It has become the core technology of modern weapons and equipment that countries focus on developing. However, with the development and progress of detection technology, the detection, tracking, and attack capabilities of defense systems in various countries are becoming stronger and stronger, and the battlefield threat environment faced by weapons and equipment is becoming more and more severe. High-efficiency combat systems have higher and higher requirements for stealth weapons and equipment. Radar absorbing material technology has developed from X- and Ku-band radar stealth of third-generation fighters to L, S, C, X, and Ku-band multi-spectrum stealth of fourth-generation fighters. However, the absorbing performance of traditional absorbing materials will be severely attenuated when it is extended to low-frequency bands, which makes it difficult for materials to achieve both low-frequency and broadband absorbing performance. Therefore, it is urgent to develop new absorbing materials with both broadband and low-frequency characteristics to meet the development needs of the next generation of weapons and equipment.
[0003] As a typical magnetic loss-type absorbing material, FeSiAl soft magnetic alloy powder is widely used in weapons and equipment. Compared with ferrite and carbonyl iron, there are no non-magnetic sub-lattices between magnetic atoms in the lattice structure of FeSiAl soft magnetic alloy, and the magnetic moments cannot cancel each other out, so it has higher saturation magnetization and permeability. FeSiAl has a high Curie temperature and good thermal stability. In addition, it has the advantages of simple preparation process and low cost, especially in the low-frequency range, it has a high Snoek limit. By flake-forming the spherical FeSiAl alloy powder, by introducing anisotropy and breaking through the limitation of the Snoek effect, the magnetic permeability of the FeSiAl alloy absorber can be further improved, and its low-frequency radar absorbing ability can be enhanced. Therefore, the flake FeSiAl soft magnetic alloy powder has good application prospects as a low-frequency radar wave absorbing material. However, the conductivity of the flake absorber is enhanced along the flake direction, resulting in an increase in the complex dielectric constant of the absorber. At high frequencies, there is a mismatch between the material characteristic impedance and the spatial characteristic impedance, which makes a large number of incident electromagnetic waves reflected on the surface of the material unable to enter the interior of the material, and it is difficult to give full play to the loss characteristics of the material. Summary of the invention
[0004] The inventors chemically modified the conductive material with dielectric dispersion characteristics (i.e., the dielectric constant decays with increasing frequency) onto the surface of FeSiAl soft magnetic alloy, thereby effectively improving the impedance matching characteristics of the material and enhancing its broadband absorption performance; furthermore, surface modification of metal organic frameworks (MOFs) was performed using polydopamine (PDA) to obtain a heterogeneous interface material with good dielectric dispersion characteristics; the two were combined to obtain an absorbing material with "thin thickness, light weight, strong absorption and wide bandwidth", thereby completing the present invention.
[0005] The object of the present invention is to provide a composite absorbing material derived from FeSiAl / MOFs with dielectric dispersion characteristics, which is composed of flaky FeSiAl alloy powder with a double functional group (-NH 2 、-Si(OC 2 H 3 ) 3 or -NH 2 、-PO(OC 2 H 3 ) 3 ) surface modifier and then coated with graphene oxide (GO) to obtain modified FeSiAl with amino functional groups on the surface, which was then reacted with the metal organic framework ZIF-67 modified with polydopamine (PDA) by heating and then subjected to high-temperature pyrolysis to obtain the obtained product.
[0006] Another object of the present invention is to provide a method for preparing a composite absorbing material derived from FeSiAl / MOFs with dielectric dispersion characteristics, the method comprising:
[0007] (1) The flaky FeSiAl alloy powder was treated with a double functional group (-NH 2 、-Si(OC 2 H 3 ) 3 or -NH 2 、-PO(OC 2 H 3 ) 3 ) surface modifier, and then coated with graphene oxide (GO) to obtain a modified FeSiAl having an amine functional group on the surface;
[0008] (2) Preparation of metal-organic framework ZIF-67 modified with polydopamine (PDA);
[0009] (3) The modified FeSiAl with a surface coating layer and the metal organic framework ZIF-67 modified with polydopamine (PDA) were heated and reacted, and then pyrolyzed at high temperature.
[0010] The present invention has the following beneficial effects:
[0011] (1) The present invention constructs a MOFs-derived porous heterostructure with dielectric dispersion characteristics on the FeSiAl surface by chemical bonding;
[0012] (2) The composite absorbing material of the present invention has wide / low frequency absorption characteristics, high absorption intensity and high absorbing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 (a) shows the absorbent FSA-H obtained in Example 1;
[0014] Figure 1 (b) shows the absorbent FSA-H obtained in Example 1;
[0015] Figure 1 (c) shows the absorbent FSA-H obtained in Example 1;
[0016] Figure 2 (a) shows the absorbent FSA-H / CoC composite material obtained in Example 2;
[0017] Figure 2 (b) shows the absorbent FSA-H / CoC composite material obtained in Example 2;
[0018] Figure 2 (c) shows the absorbent FSA-H / CoC composite material obtained in Example 2;
[0019] Figure 3 (a) shows the absorbent FSA-H / rGO / CoC composite material obtained in Example 3;
[0020] Figure 3 (b) shows the absorbent FSA-H / rGO / CoC composite material obtained in Example 3;
[0021] Figure 3 (c) shows the absorbent FSA-H / rGO / CoC composite material obtained in Example 3;
[0022] Figure 4 (a) shows the absorbent FSA-H / rGO / CoC-N composite material obtained in Example 4;
[0023] Figure 4 (b) shows the absorbent FSA-H / rGO / CoC-N composite material obtained in Example 4;
[0024] Figure 4 (c) shows the absorbent FSA-H / rGO / CoC-N composite material obtained in Example 4;
[0025] Figure 5(a) shows the absorbent FSA-P / rGO / CoC-N composite material obtained in Example 5;
[0026] Figure 5 (b) shows the absorbent FSA-P / rGO / CoC-N composite material obtained in Example 5;
[0027] Figure 5 (c) shows the absorbent FSA-P / rGO / CoC-N composite material obtained in Example 5;
[0028] Figure 6 The dielectric real part data of electromagnetic parameters of the samples of the embodiment are shown;
[0029] Figure 7 The dielectric imaginary part data of electromagnetic parameters of the samples of the embodiment are shown;
[0030] Figure 8 The real part data of the electromagnetic parameters and magnetic permeability of the samples of the embodiment are shown;
[0031] Fig. 9 The imaginary part data of the electromagnetic parameters and magnetic permeability of the example samples are shown. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present invention will become more clear and distinct.
[0033] In the present invention, a dielectric dispersion conductive material, such as a carbon-based material, whose dielectric constant decays as the frequency increases, is chemically modified to the surface of a magnetic metal FeSiAl soft magnetic alloy, and the magnetic metal FeSiAl soft magnetic alloy is endowed with dielectric dispersion characteristics through the flow of carriers between the two, so that the dielectric constant value also decreases as the frequency increases, thereby effectively improving the impedance matching characteristics and enhancing the broadband absorption performance; after pyrolysis, the metal ions of ZIF-67 modified with polydopamine (PDA) can be converted into metal elements or metal oxides, and the organic ligands can form a conductive carbon layer, thereby effectively increasing the magnetic loss and dielectric loss characteristics of the material, and the dielectric dispersion characteristics are excellent. The above is a possible speculation on the principle of the present invention, and the present invention is not limited thereto.
[0034] In a preferred embodiment of the present invention, the flaky FeSiAl alloy powder is treated with a bifunctional group (-NH 2 、-Si(OC 2 H 3 ) 3 or -NH 2 、-PO(OC 2 H 3 ) 3) surface modifier and then graphene oxide (GO) surface coating process includes: bifunctional surface modifier and flaky FeSiAl alloy powder are sequentially added into 95% ethanol solution, heated to react, so that the surface modifier is evenly modified on the FeSiAl surface, and then the modified FeSiAl is added into GO dispersion, heated to react, and the surface GO is coated to obtain modified FeSiAl (denoted as FeSiAl@GO) with amino functional groups on the surface.
[0035] In the present invention, as a bifunctional group (-NH 2 、-Si(OC 2 H 3 ) 3 or -NH 2 、-PO(OC 2 H 3 ) 3 ) surface modifier, aminosiloxanes such as γ-aminopropyltriethoxysilane (KH550); γ-aminopropyltrimethoxysilane; γ-aminopropylmethyldiethoxysilane); aminophosphoric acid esters such as O,O-dimethyl-2-methylcarbamoyl-1-methylvinyl phosphate; O,O-dimethyl-S-(N-methylcarbamoylmethyl)thiophosphate; O,O-dimethyl-S-(methylcarbamoylmethyl) dithiophosphate can be used.
[0036] In the present invention, as the flaky FeSiAl alloy powder, a common FeSiAl alloy powder can be used. Preferably, a flaky FeSiAl alloy powder with a particle size of 3 to 10 μm is used.
[0037] The amount of the bifunctional surface modifier used for modification is preferably 0.1-5wt% of the flaky FeSiAl alloy powder, and more preferably 1-3wt%, in which case the surface modification effect is better.
[0038] In the present invention, the modification reaction is preferably carried out at a temperature of 60-80°C, more preferably 70°C; the reaction time is not particularly limited, but is preferably 2-8 hours, more preferably 6 hours.
[0039] In the present invention, the amount of graphene oxide used is 0.5-10wt%, preferably 5wt%, relative to the weight of the surface-modified FeSiAl.
[0040] In the GO surface protective layer coating, the ultrasonic dispersion time is preferably 0.5-2 hours, such as 1 hour; the heating reaction temperature in an inert gas atmosphere, such as a nitrogen atmosphere, is preferably 80-100°C, preferably 95°C.
[0041] In a preferred embodiment of the present invention, the process for preparing the metal organic framework ZIF-67 modified with polydopamine (PDA) comprises: 3 ) 2 6H 2 O and dimethylimidazole (2-MeIM) were dissolved in methanol, and the transparent 2-MeIM methanol solution was poured into Co(NO 3 ) 2 6H 2 O methanol solution, stirring and mixing evenly, and letting it stand to obtain ZIF-67; ZIF-67 is dispersed in methanol, dopamine (DA) is added to the methanol dispersion of ZIF-67, and stirred to obtain a polydopamine (PDA)-modified metal organic framework ZIF-67 (denoted as ZIF-67@PDA).
[0042] In the present invention, the preparation process of ZIF-67 can be based on the existing preparation process, for example, 0.249 g Co(NO 3 ) 2 6H 2 O and 0.328 g of dimethylimidazole (2-MeIM) were dissolved in 25 mL of anhydrous methanol. Under magnetic stirring, the transparent 2-MeIM solution was poured into the Co(NO 3 ) 2 6H 2 O solution, stirred thoroughly, mixed evenly and then allowed to stand for 24 hours to obtain the product ZIF-67. The product was centrifuged and washed three times with anhydrous methanol, and dried at 60°C with forced air to constant weight to obtain ZIF-67 powder.
[0043] In the present invention, the amount of dopamine used for modification is preferably 0.5-5wt%, more preferably 1-3wt% of the ZIF-67 powder.
[0044] To promote the modification of dopamine, magnetic stirring is preferred, and the stirring reaction time is more than 10 hours, for example 12 hours.
[0045] In a preferred embodiment of the present invention, the heating reaction and high-temperature pyrolysis process of the modified FeSiAl having an amine functional group on the surface and the metal organic framework ZIF-67 modified with polydopamine (PDA) include: ultrasonic mixing and heating reaction of the modified FeSiAl (FeSiAl@GO) having a graphene oxide surface protection layer and the metal organic framework ZIF-67 modified with polydopamine (PDA) (denoted as ZIF-67@PDA), and obtaining a heterostructure material (denoted as FeSiAl@GO / ZIF-67@PDA) through the reaction between the epoxy group of GO and the amine group on PDA. Then, high-temperature pyrolysis is carried out at a temperature of 500°C-800°C under a nitrogen atmosphere to obtain a FeSiAl / MOFs-derived composite absorbing material (denoted as FSA-H / rGO / CoC-N) with dielectric dispersion characteristics.
[0046] In the present invention, the amount of modified FeSiAl (FeSiAl@GO) having amino functional groups on the surface is preferably 25-75% of the mass of the metal organic framework ZIF-67 (denoted as ZIF-67@PDA) modified with polydopamine (PDA), and more preferably 40-50%; the reaction of the two is carried out at 80-100°C, preferably 95°C.
[0047] In the present invention, high-temperature pyrolysis is preferably carried out in a tubular furnace, the heating rate of the tubular furnace is preferably 2-5°C / min, the pyrolysis temperature is 500-800°C, preferably 700°C, and the high-temperature pyrolysis reaction insulation time is preferably 1-4 hours, for example 2 hours.
[0048] Example 1
[0049] 0.15 g of bifunctional surface modifier γ-aminopropyltriethoxysilane (KH550) and 5 g of flaky FeSiAl alloy powder (FeSiAl flaky magnetic powder, Fe: 85%, Si:
[0050] 9.6%, Al: 5.4% (all by mass fraction, Xi'an Hongyuan Electronic Materials Co., Ltd.) were added to 20mL 95% ethanol solution in sequence. Reacted under 70°C oil bath heating conditions for 6 hours to uniformly modify the surface modifier on the FeSiAl surface. The obtained product was filtered and placed in an 80°C oven for drying for 24 hours. A tubular furnace was used in a nitrogen atmosphere, with a heating rate of 2°C / min and kept warm at 700°C for 2 hours. Surface-modified FSA-H was obtained. Then, 30% FSA-H was mixed with paraffin (0.3g FSA-H, 0.7g paraffin) to test its wave absorption performance. Its reflectivity is shown in the attached figure. Figure 1 .
[0051] Example 2
[0052] 0.15g of bifunctional surface modifier γ-aminopropyltriethoxysilane (KH550) and 5g of flaky FeSiAl alloy powder were added to 20mL of 95% ethanol solution in sequence. The mixture was heated in an oil bath at 70°C for 6 hours to uniformly modify the surface modifier on the FeSiAl surface. The obtained product was filtered and dried in an oven at 80°C for 24 hours to obtain surface-modified FeSiAl-H.
[0053] 0.249 g Co(NO 3 ) 2 6H 2 O and 0.328 g 2-MeIM were dissolved in 25 mL of anhydrous methanol. Under magnetic stirring, the transparent 2-MeIM solution was poured into the Co(NO 3 ) 2 6H 2 O solution, stirred thoroughly, mixed evenly and then allowed to stand for 24 hours. The product was washed three times by centrifugation with anhydrous methanol and dried at 60°C to constant weight to obtain ZIF-67 powder.
[0054] 0.75g of surface-modified FeSiAl-H was ultrasonically mixed with 1.5g of ZIF-67 and heated in an oil bath at 95°C to obtain FeSiAl-H / ZIF-67. A tubular furnace was used in a nitrogen atmosphere to heat at 700°C for 2h at a heating rate of 2°C / min to obtain a surface-modified FSA-H / CoC composite material. The surface-modified FSA-H / CoC composite material was then mixed with paraffin at a dosage of 30% (0.3g FSA-H / CoC composite material, 0.7g paraffin) to test its wave absorption performance. Its reflectivity is shown in the attached figure. Figure 2 .
[0055] Example 3
[0056] 0.15g of bifunctional surface modifier γ-aminopropyltriethoxysilane (KH550) and 5g of flaky FeSiAl alloy powder were added to 20mL of 95% ethanol solution in sequence. The reaction was carried out under 70°C oil bath heating conditions for 6 hours to uniformly modify the surface modifier on the FeSiAl surface. The obtained product was filtered and placed in an 80°C oven for drying for 24 hours to obtain surface-modified FeSiAl. 3g of modified FeSiAl was added to 0.15g (GO mass) of GO prepared dispersion (1mg / mL), mixed and ultrasonically dispersed for 1h, and heated in a 95°C oil bath to obtain FeSiAl-H@GO.
[0057] 0.249 g Co(NO 3 ) 2 6H 2O and 0.328 g 2-MeIM were dissolved in 25 mL of anhydrous methanol. Under magnetic stirring, the transparent 2-MeIM solution was poured into the Co(NO 3 ) 2 6H 2 O solution, stirred thoroughly, mixed evenly and then allowed to stand for 24 hours. The product was washed three times by centrifugation with anhydrous methanol and dried at 60°C to constant weight to obtain ZIF-67 powder.
[0058] 0.75g of surface-modified FeSiAl-H@GO was ultrasonically mixed with 1.5g of ZIF-67 and heated in an oil bath at 95°C to obtain FeSiAl-H@GO / ZIF-67. A tubular furnace was used in a nitrogen atmosphere to heat at 700°C for 2h at a heating rate of 2°C / min to obtain a surface-modified FSA-H / rGO / CoC composite material. The surface-modified FSA-H / rGO / CoC composite material was then mixed with paraffin at a dosage of 30% (0.3g FSA-H / rGO / CoC composite material, 0.7g paraffin) to test its wave absorption performance. Its reflectivity is shown in the attached figure. Figure 3 .
[0059] Example 4
[0060] 0.15g of bifunctional surface modifier γ-aminopropyltriethoxysilane (KH550) and 5g of flaky FeSiAl alloy powder were added to 20mL of 95% ethanol solution in sequence. The reaction was carried out under 70℃ oil bath heating conditions for 6 hours to uniformly modify the surface modifier on the FeSiAl surface. The obtained product was filtered and placed in an 80℃ oven for 24h to obtain surface-modified FeSiAl-H. 3g of modified FeSiAl-H was added to 0.15g (GO mass) of GO prepared dispersion (1mg / mL), mixed and ultrasonically dispersed for 1h, and heated in a 95℃ oil bath under a nitrogen atmosphere to obtain FeSiAl-H@GO.
[0061] 0.249 g Co(NO 3 ) 2 6H 2 O and 0.328 g 2-MeIM were dissolved in 25 mL of anhydrous methanol. Under magnetic stirring, the transparent 2-MeIM solution was poured into the Co(NO 3 ) 2 6H 2O solution, stir thoroughly, mix evenly and let stand for 24 hours. The product was washed three times by centrifugation with anhydrous methanol, dried at 60°C to constant weight, and ZIF-67 powder was obtained. 300 mg ZIF-67 was dispersed in 45 mL anhydrous methanol, 9 mg dopamine (DA) was added to the ZIF-67 dispersion, and magnetic stirring was performed for 12 hours. Anhydrous methanol was used for multiple dispersions, centrifugal washing, and the obtained precipitate was dried in a vacuum oven at 60°C to constant weight to obtain the product ZIF-67@PDA.
[0062] 0.75g of surface-modified FeSiAl-H@GO was ultrasonically mixed with 1.5g of ZIF-67@PDA and heated in an oil bath at 95°C. FeSiAl-H@GO / ZIF-67@PDA was prepared. A tubular furnace was used in a nitrogen atmosphere at a heating rate of 2°C / min and the mixture was kept at 700°C for 2h to obtain a surface-modified FSA-H / rGO / CoC-N composite material. The surface-modified FSA-H / rGO / CoC-N composite material was then mixed with paraffin at a dosage of 30% (0.3g FSA-H / rGO / CoC-N composite material, 0.7g paraffin) to test its wave absorption performance. The reflectivity is shown in the attached figure. Figure 4 .
[0063] Example 5
[0064] 0.15g of bifunctional surface modifier O,O-dimethyl-2-methylcarbamoyl-1-methylvinyl phosphate and 5g of flaky FeSiAl alloy powder were added to 20mL of 95% ethanol solution. The reaction was carried out under 70℃ oil bath heating conditions for 6 hours to uniformly modify the surface modifier on the FeSiAl surface. The obtained product was filtered and dried in an 80℃ oven for 24h to obtain FeSiAl-P with phosphate surface modification. 3g of modified FeSiAl was added to the dispersion (1mg / mL) prepared by 0.15g (GO mass) GO, mixed and ultrasonically dispersed for 1h, and heated in 95℃ oil bath to obtain FeSiAl-P@GO.
[0065] 0.249 g Co(NO 3 ) 2 6H 2 O and 0.328 g 2-MeIM were dissolved in 25 mL of anhydrous methanol. Under magnetic stirring, the transparent 2-MeIM solution was poured into Co(NO 3 ) 2 6H 2O solution, stir thoroughly, mix evenly and let stand for 24 hours. The product was washed three times by centrifugation with anhydrous methanol, dried at 60°C to constant weight, and ZIF-67 powder was obtained. 300 mg ZIF-67 was dispersed in 45 mL anhydrous methanol, 9 mg dopamine (DA) was added to the ZIF-67 dispersion, and magnetic stirring was performed for 12 hours. Anhydrous methanol was used for multiple dispersions, centrifugal washing, and the obtained precipitate was dried in a vacuum oven at 60°C to constant weight to obtain the product ZIF-67@PDA.
[0066] 0.75g of FeSiAl-P@GO modified with phosphate was ultrasonically mixed with 1.5g of ZIF-67@PDA and heated in an oil bath at 95°C. FeSiAl-P@GO / ZIF-67@PDA was prepared. A tubular furnace was used in a nitrogen atmosphere at a heating rate of 2°C / min and the mixture was kept at 700°C for 2h to obtain a FSA-P / rGO / CoC-N composite material modified with phosphate. The FSA-P / rGO / CoC-N composite material modified with 30% phosphate was then mixed with paraffin (0.3g of FSA-P / rGO / CoC-N composite material modified with phosphate, 0.7g of paraffin) to test its wave absorption performance. The reflectivity is shown in the attached figure. Figure 5 .
[0067] Test example
[0068] Powders 1-5 were uniformly dispersed in paraffin, and concentric rings with an outer diameter of 7.00 mm and an inner diameter of 3.04 mm were made by molding. The electromagnetic parameters of the samples were tested at a frequency of 2-18 GHz using a vector network analyzer (Agilent E5071C).
[0069] Table 1
[0070]
[0071] The present invention is described in detail above in conjunction with specific embodiments and / or exemplary examples and drawings, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A composite absorbing material derived from FeSiAl / MOFs with dielectric dispersion characteristics, which is prepared by modifying flaky FeSiAl alloy powder with a bifunctional surface modifier and then coating it with graphene oxide (GO) to obtain a modified FeSiAl with amino functional groups on the surface, which is then heated and reacted with a metal organic framework ZIF-67 modified with polydopamine (PDA) and then subjected to high-temperature pyrolysis to obtain the modified FeSiAl.
2. A method for preparing a composite absorbing material derived from FeSiAl / MOFs with dielectric dispersion characteristics, the method comprising the following steps: (1) The flaky FeSiAl alloy powder is modified by a bifunctional surface modifier, and then coated with graphene oxide (GO) to obtain a modified FeSiAl having an amine functional group on the surface; (2) Preparation of metal-organic framework ZIF-67 modified with polydopamine (PDA); (3) The modified FeSiAl with amino functional groups on the surface and the metal organic framework ZIF-67 modified with polydopamine (PDA) were heated and reacted, and then pyrolyzed at high temperature.
3. The method of claim 2, wherein: Step (1) comprises: adding a bifunctional surface modifier and a flaky FeSiAl alloy powder to a 95% ethanol solution in sequence, heating the solution to allow the surface modifier to be evenly modified on the FeSiAl surface, adding the modified FeSiAl to a GO dispersion, ultrasonically dispersing the solution, heating the solution to allow the surface GO protective layer to be coated, and obtaining a modified FeSiAl having a GO surface protective layer.
4. The method of claim 3, wherein: As bifunctional surface modifiers, use is made of: aminosiloxanes such as γ-aminopropyltriethoxysilane (KH550); γ-aminopropyltrimethoxysilane; γ-aminopropylmethyldiethoxysilane); aminophosphoric acid esters such as O,O-dimethyl-2-methylcarbamoyl-1-methylvinyl phosphate; O,O-dimethyl-S-(N-methylcarbamoylmethyl)thiophosphate; O,O-dimethyl-S-(methylcarbamoylmethyl)dithiophosphate.
5. The method of claim 3, wherein: The amount of graphene oxide used is 0.5-10wt% relative to the weight of the surface-modified FeSiAl.
6. The method of claim 2, wherein: Step (2) comprises: dissolving Co(NO3)2·6H2O and dimethylimidazole (2-MeIm) in methanol respectively, mixing transparent dimethylimidazole evenly under magnetic stirring conditions, and standing to obtain ZIF-67; dispersing ZIF-67 in methanol, adding dopamine (DA) to the methanol dispersion of ZIF-67, stirring, and obtaining a polydopamine (PDA)-modified metal organic framework ZIF-67.
7. The method of claim 6, wherein: The amount of dopamine used for modification is preferably 0.5-5 wt % of the ZIF-67 powder.
8. The method of claim 2, wherein: Step (3) comprises: ultrasonically mixing the modified FeSiAl with amino functional groups on the surface and the metal organic framework ZIF-67 modified with polydopamine (PDA), heating the reaction, obtaining a heterostructure material through the reaction between the epoxy groups of GO and the amino groups on PDA, and then performing high-temperature pyrolysis at a temperature of 500° C. to 800° C. in a nitrogen atmosphere to obtain a FeSiAl / MOFs-derived composite absorbing material with dielectric dispersion characteristics.
9. The method of claim 8, wherein: The amount of the modified FeSiAl having an amine functional group on the surface is 25-75% of the mass of the metal organic framework ZIF-67 modified with polydopamine (PDA).